The Decline and Recovery of a Crab Population From an Extreme Marine Heatwave and a Changing Climate - Chandrapavan, Arani; Caputi, Nick; Kangas, Mervi I. (Frontiers in Marine Science, 2019)
Driven by a very strong La Niña event and a record strength Leeuwin Current, the 2011 Western Australian marine heatwave (MHW) raised sea surface temperatures (SSTs) along the Western Australian coastline up to 5oC between November 2010 and March 2011. This single thermal perturbation led to several mortality events and recruitment impairment of commercially important species including Australia’s single highest producing blue swimmer crab (Portunus armatus) fishery in Shark Bay. Monthly catch landings dramatically declined from 166 t in April 2011 to <10 t by December 2011 promoting its closure in 2012 to allow for stock recovery. Examination of stock-environment relationships critical to the recruitment of blue swimmer crabs living towards their thermal maxima, showed juvenile P. armatus to be most susceptible to heat stress when mean water temperatures between December and January were greater than 24°C, and detrimental when they exceed 26°C as was the case during the 2011 MHW when SSTs reached 29°C. Partial recovery of the crab stock 18 months after the MHW was strongly associated with mean summer temperatures returning below 24°C. Together with a change in management to a quota system, the fishery returned to full recovery status in 2018 with sustainable catch levels of up to 550 t. Long term fishery productivity is now at high risk from climate change impacts with shifts in winter water temperatures being cooler by 2°C and occurring earlier by few months inside the Bay. This cooling trend appears to be impacting the spawning period with the timing of peak recruitment also occurring earlier, shifting from February to November. The impacts of the 2011 MHW highlighted the risk to stock sustainability through external drivers such as climate change that was previously poorly understood. Therefore, responding to climate change is now about managing risks to achieve a balance between fisheries sustainability and economic viability. Increased stock monitoring now provides biomass measures 12 months prior to the fishing season, a form of stock forecasting that stakeholders can utilise to better manage their fishing business and minimise economic loss, while a flexible harvest strategy now responds to recruitment variation and climate extremes.